A facile way for scalable fabrication of silver nanowire network electrodes for high-performance and foldable smart windows. Issue 17 (22nd April 2020) - Huang, Shengyun; Zhang, Qingzhe; Yang, Fan; Gangadharan, Deepak Thrithamarassery; Li, Pandeng; Ren, Fuqiang; Sun, Baoquan; Ma, Dongling
Abstract : Ag NW TCE based SPDs show high performance (optical modulation 60.2%; switching time 21 s) and excellent flexibility (folded 180°). Abstract : Large-area, free-standing silver (Ag) nanowire (NW) transparent conductive electrodes (TCEs) are fabricated by a facile and high-throughput automatic-blade-coating assembly technique, enabled by the use of a flexible and transparent polymer matrix. Such developed TCEs exhibit high transparency, excellent conductivity, superior flexibility, long-term stability and strong structural integrity. The excellent flexibility allows the TCEs to be bent >10 000 times without any performance degradation. As a proof of concept, these TCEs are used to fabricate flexible suspended particle devices (SPDs) for smart window applications. Our devices show a large change in their optical transmittance (60.2%) and fast switching time (21 s) as well as excellent stability, comparable to the best SPD performance data reported in the literature. Moreover, significantly better than commercial TCE-based devices, the SPDs based on our TCEs show excellent mechanical flexibility, which can be folded by 180° for more than 200 cycles without any obvious performance degradation. The present method for fabricating large area and ultra-flexible Ag NW TCEs may be extended to fabricate various NW-based nonplanar or curved electronic/optoelectronic devices in the future.